Potentially modifiable risk factors of frailty in community-dwelling older fallers - Toh, Wen Shien (2017)
Background and Aim: Falls in the older adult are associated with significant morbidity, functional decline and institutionalization. As the population ages, falls are likely to increase in incidence. Thus, prevention is a key public health objective. Frailty, given its association with increased fall risk, could be an entity to be screened for and targeted. The aim of this study is to characterize the differences between frail and non-frail fallers, and thus identify potentially modifiable risk factors. It is hypothesized that differences in falls profile, physical, psychiatric, functional, nutritional indicators and co-morbidities would exist. Methods: A cross-sectional analysis of 58 community-dwelling older fallers was performed. They were screened for pre-frailty or frailty using the FRAIL questionnaire, then classified via objective assessment into frail and non-frail based on an adaptation of Fried’s frailty criteria. Subjects’ baseline characteristics were evaluated, including falls history, physical performance and endurance tests, scoring of cognition and mood, questionnaires to assess function, laboratory investigations for nutrition and review of co-morbidities. Results: 70.7% of fallers were non-frail, while 29.3% were frail. Both groups did not significantly differ in terms of age, gender and ethnicity. Cognitive impairment, determined by a lower Chinese Mini-Mental State Examination (CMMSE) score, was associated with increased risk of physical frailty. Depressive symptoms, measured by the Geriatric Depression Scale (GDS) were also linked with frailty. Frail fallers had impaired physical performance and endurance, and more fall risk factors. When adjusted for age and gender, lower CMMSE scores (OR=0.864, p=0.045) remained independently associated with frailty. Frailty is not synonymous with functional decline or co-morbidity, as differences in these domains were not significant. Conclusion: Frailty predicts potentially modifiable risk factors in the physical and psychiatric domain. Thus, it is a syndrome that should be screened for and targeted as part of a holistic falls prevention programme.